Identifying patients at risk of vitamin D deficiency in juvenile idiopathic arthritis - E.N. Mukvich; L.I. Omelchenko; I.V. Dudka; E.A. Belskaya; N.N. Vdovina; N.B. Macyuk; A.N. Mackevich; T.A. Lyudvik; D.L. Ismakaieva (Zaslavsky O.Yu., 2021)
Background. The purpose was to determine the risk factors for reducing the provision of vitamin D (VD) in patients with juvenile idiopathic arthritis (JIA) and to develop a questionnaire for the rapid identification of children who require monitoring the concentration of 25OHD in the blood. Materials and methods. Clinical and laboratory examination of 78 children aged 2-17 years with JIA was performed. General clinical, biochemical, statistical methods and standardized criterion testing were used. Results. The most unfavorable risk factors for reducing VD provision in children with JIA have been identified, a questionnaire has been developed that can be used to identify people at high VD deficiency. Risk factors are evaluated in points. When questioning individuals with JIA, the total number of points obtained by each patient was determined. In children, who have received more than 264 points, VD insufficiency or deficiency is confirmed laboratorially. The electronic version of the questionnaire is created in the online service for remote testing with the ability to view results for each respondent separately and to identify patients at high risk of vitamin D deficiency. The questionnaire also allows separating groups of patients at risk of VD insufficiency for further monitoring of 25OHD concentrations in the blood serum, which is useful in clinical practice of children's rheumatologist, pediatrician and family physician. Conclusions. In patients with JIA, it is necessary to determine the risk factors for reducing VD provision in the body to identify individuals who require the evaluation of its concentration in the blood with subsequent monitoring. A questionnaire has been developed that allows us to collect information on the risks of developing VD insufficiency, assess them and determine the basic cohort of patients for laboratory studies and deciding whether to prescribe vitamin D preparations to them.